2017
DOI: 10.1186/s13059-017-1162-x
|View full text |Cite
|
Sign up to set email alerts
|

RNAs competing for microRNAs mutually influence their fluctuations in a highly non-linear microRNA-dependent manner in single cells

Abstract: BackgroundDistinct RNA species may compete for binding to microRNAs (miRNAs). This competition creates an indirect interaction between miRNA targets, which behave as miRNA sponges and eventually influence each other’s expression levels. Theoretical predictions suggest that not only the mean expression levels of targets but also the fluctuations around the means are coupled through miRNAs. This may result in striking effects on a broad range of cellular processes, such as cell differentiation and proliferation.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
3
3

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 60 publications
(82 reference statements)
4
52
0
Order By: Relevance
“…Previous studies were mainly focused on the role of miRNAs but neglected the miRNA-mediated cross-talk among competing targets. Recent works have found that the cross-talk among competing targets could enhance the stability of gene expression [13,14,45]. Here, we observed a positive correlation between the abundance of targets pool and noise reduction ( Fig.…”
Section: Discussionsupporting
confidence: 70%
“…Previous studies were mainly focused on the role of miRNAs but neglected the miRNA-mediated cross-talk among competing targets. Recent works have found that the cross-talk among competing targets could enhance the stability of gene expression [13,14,45]. Here, we observed a positive correlation between the abundance of targets pool and noise reduction ( Fig.…”
Section: Discussionsupporting
confidence: 70%
“…The introduction of R (miRNA) as repressor can decrease the noise of lowly expressed genes, meanwhile generate a noise peak in the "R near-equimolar" regime for highly expressed genes ( Fig. 5A), consistent with previous studies (41,42).…”
Section: Competition Can Modify Target Expression Noise Levelsupporting
confidence: 90%
“…We also recalled that the system Eq (2) possesses a unique, asymptotically stable steady state [64]. However, both theoretical and experimental studies have shown that miRNAs, in peculiar conditions of stoichiometry, induce bimodal distributions in the expression level of their targets [45,60,78]. As reviewed in [79] and shown in [80], some biological systems may present bimodality just as a consequence of stochasticity and despite being monostable at the deterministic level.…”
Section: Emergence Of Bimodal Gene Expressionmentioning
confidence: 96%